Care Levels for Fetal Therapy Centers. Issue 4 (21st December 2022) - Baschat, A.A.; Blackwell, S.B.; Chatterjee, D.; Cummings, J.J.; Emery, S.P.; Hirose, S.; Hollier, L.M.; Johnson, A.; Kilpatrick, S.J.; Luks, F.I.; Menard, M.K.; McCullough, L.B.; et al.
Abstract : ( Obstet Gynecol . 2022;139:1027–1042. doi: 10.1097/AOG.0000000000004793) Fetal therapy carries both benefits and extensive risks for the fetus and pregnant patient. As such, outlines created by several different groups and organizations are used throughout the country, but these general guidelines do not anticipate the needs of individual circumstances. This article recommends certain parameters for resources at fetal therapy centers in order to provide both pregnant patients and their fetus with an adequate level of care.